IMPLEMENTASI ALGORITMA NAIVE BAYES UNTUK MENENTUKAN TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK (STUDI KASUS : BALAI PENGKAJIAN TEKNOLOGI PERTANIAN DAERAH ISTIMEWA YOGYAKARTA) - Hartatik; Dwi Lestari (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
Public services by this government apparatus are still found in weaknesses so that they cannot meet the quality expected by the community. This was marked by the existence of various public complaints that were conveyed through the mass media, so as to create an unfavorable image of the government apparatus. This research was conducted in making a prediction system by utilizing the Naïve Bayes algorithm. It can be seen the level of community satisfaction based on index values obtained from the results of quantitative and qualitative measurements of public opinion at the Yogyakarta Institute of Agricultural Technology and the level of accuracy in implementing Naïve Bayes algorithms.From the results that have been known, it can be used as a benchmark to assess the level of service quality at the Yogyakarta Institute of Agricultural Technology Assessment, with the aim of knowing the level of performance of service units on a regular basis as material to establish policies in order to improve the quality of subsequent public services and the government can continue to improve service quality